Estudo e avaliação de uma proposta de modelagem do comportamento micromecânico do concreto - Borges, Dannilo Carvalho (2015)
This work deals with a proposed numerical modeling of mechanical behavior in brittle heterogeneous materials, such as concrete. For this propose, a two-dimensional meso-scale model is presented. The material is considered as a three-phase material consisting of interface zone, matrix and inclusions – each constituent modeled by an appropriate constitutive model. The Representative Volume Element (RVE) consists of inclusions idealized as circular shapes randomly placed into the RVE. The interface zone is modeled by means of cohesive contact finite elements the inclusions are considered as linear elastic media and matrix region is considered as elastoplastic material. The main goal here is to show that simple constitutive modeling of the microstructure can be employed with a computational homogenization-based approach as an alternative to complex macroscopic constitutive models for the mechanical behavior of the heterogeneous materials using a finite element procedure within a purely kinematical multi-scale framework. A set of numerical examples, involving the microcracking and plasticity processes, is provided in order to illustrate the qualitative performance of the proposed modeling.